1994
DOI: 10.1038/ki.1994.112
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of low protein-normal sodium diet on renal function in chronic renal failure

Abstract: To investigate the short-term renal effects of protein restriction and unchanged salt intake in chronic renal failure (CRF), patients with moderate CRF (creatinine clearance 41 +/- 5 ml/min) and healthy controls (CON) ate a normal protein diet (NPD) for four weeks, and thereafter a low protein diet (LPD, 0.4 g/kg body wt/day) for three weeks. The two diets were isocaloric and with a salt intake of 10 to 13 g/day. No differences in body weight, serum proteins and plasma sodium were recorded throughout the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…On the other hand, a previous study by our group indicates that the isolated restriction of protein intake, that is, in the presence of constantly normal salt intake, does not induce any change of mean BP values in CKD patients. 30 Overall, these data identify the moderate reduction of salt intake, with the dependent partial correction of extracellular volume expansion, as a relevant determinant of BP decrease during VLPD. In addition, other authors have evidenced that moderate dietary sodium restriction rapidly normalizes BP in patients with systolic hypertension also by improving large elastic artery compliance.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, a previous study by our group indicates that the isolated restriction of protein intake, that is, in the presence of constantly normal salt intake, does not induce any change of mean BP values in CKD patients. 30 Overall, these data identify the moderate reduction of salt intake, with the dependent partial correction of extracellular volume expansion, as a relevant determinant of BP decrease during VLPD. In addition, other authors have evidenced that moderate dietary sodium restriction rapidly normalizes BP in patients with systolic hypertension also by improving large elastic artery compliance.…”
Section: Discussionmentioning
confidence: 67%
“…Recent data from our group actually confute this hypothesis. We have demonstrated that in patients with moderate CRF, renal hemodynamics do not change when a LPD is started while maintaining a constant salt intake [19]; conversely, a decrease of renal perfusion and GFR becomes evident if patients undergo salt restriction in the presence of a constant protein intake [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a longer follow-up would have been required to reach statistical significance. Interestingly, with regards to the acute GFR response to a low-protein diet, we have previously demonstrated by means of inulin and PAH clearance studies that, in CKD patients (basal GFR around 40 mL/min), reduced protein intake per se does not translate in acute decline in GFR if salt intake is kept constant [ 60 ]. In contrast, low salt intake in the presence of constant protein intake is associated with a GFR reduction of 6 mL/min on average related to reductions in ECV and BP [ 61 ].…”
Section: The Check-mark Sign: Not Only Sglt2imentioning
confidence: 99%